Fundamental and Research Frontier of Atmospheric Corrosion - Manuel Morcillo (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Metallic corrosion is an expensive problem in industrialised countries, creating annual costs that are equivalent to around 3.5% of GDP. More than half of this amount is attributable to atmospheric corrosion. A large amount of scientific and technical literature has been published in the field of atmospheric corrosion, and numerous books and many general treatises have focused on this topic. In the period between 1970-2000 ASTM-STP made great efforts to disseminate progress in this field through the periodic publication of monographies and organisation of symposia on atmospheric corrosion. This special issue of Materials (MDPI) brings together the state of the art in this field, highlighting the advances made in the last fifteen years and identifying the areas where future research will need to concentrate. This publication is intended not only for researchers in the field of atmospheric corrosion, but also for technicians in charge of the design and maintenance of metallic items or concerned with their integrity and duration in the atmosphere.